Dissecting the Mechanism of Histone Deacetylase Inhibitors to Enhance the Activity of Zinc Finger Nucleases Delivered by Integrase-Defective Lentiviral Vectors - Joglekar, Alok V. (Mary Ann Liebert, Inc., 2014)
Integrase-defective lentiviral vectors (IDLVs) have been of limited success in the delivery of zinc finger nucleases (ZFNs) to human cells, due to low expression. A reason for reduced gene expression has been proposed to involve the epigenetic silencing of vector genomes, carried out primarily by histone deacetylases (HDACs). In this study, we tested valproic acid (VPA), a known HDAC inhibitor (HDACi), for its ability to increase transgene expression from IDLVs, especially in the context of ZFN delivery. Using ZFNs targeting the human adenosine deaminase (ADA) gene in K562 cells, we demonstrated that treatment with VPA enhanced ZFN expression by up to 3-fold, resulting in improved allelic disruption at the ADA locus. Furthermore, three other U.S. Food and Drug Administration-approved HDACis (vorinostat, givinostat, and trichostatin-A) exhibited a similar effect on the activity of ZFN-IDLVs in K562 cells. In primary human CD34(+) cells, VPA- and vorinostat-treated cells showed higher levels of expression of both green fluorescent protein (GFP) as well as ZFNs from IDLVs. A major mechanism for the effects of HDAC inhibitors on improving expression was from their modulation of the cell cycle, and the influence of heterochromatinization was determined to be a lesser contributing factor.